Static and Dynamic Tests of the Railway Subgrade Construction Model - Jan Lelak; Dusan Slavik; Martin Mecar (Communications - Scientific letters of the University of Zilina, 2004)
The presented paper deals with the research of railway subgrade construction. The purpose was to compare static and dynamic modulus of deformation namely on two different railway subgrade constructions. The effect of reinforcing geosynthetics was found out as well, when a different type of reinforcing geosynthetics was used.